Naphazoline poisoning associated with bradycardia and persistent hypertension: Case report - Dreckmann, Marcelo Vitola; Lima , Paloma Farina de; Cruz, Eduardo; Amaral , Felipe Barbosa; Ramos, Victoria Schmidt; Linhares, Marcelo José; Schulz, Julio Cesar; Gardenghi, Giulliano (JOURNAL OF CARDIAC ARRHYTHMIAS, 2024)
Naphazoline (NA) is an α-adrenergic agonist derived from imidazoline. Due to its vasoconstrictor action, it is widely used as a nasal decongestant with a rapid onset of action. It presents few studies on its side effects, with most case studies of accidental ingestion in children under two years of age. We report a case on the relationship between NA intoxication and symptomatic bradycardia, reversed after administration of intravenous Naloxone, in a young adult patient.